Capacidades motoras e participação em casa de lactentes de risco biológico no primeiro ano de vida: impacto de fatores ambientais considerando a pandemia da COVID-19 - Abreu, Raissa Wanderley Ferraz de (2021)
According to the International Classification of Functioning, Disability and Health (ICF), functionality results from the positive interaction between the components of body structure and function, activity and participation, under the influence of environmental factors. In this context, the importance of biopsychosocial assessment in biological risk infants is highlighted, since activities and participation can be impacted by adversities at birth, possible predictors of disability, as well as by environmental barriers. Among the various environmental factors (social, physical and attitudinal) the current scenario of the pandemic is emphasized, with Social Distancing (SD) as likely for the development of infants, especially those with biological vulnerability. In view of this, there was a motivation to prepare a systematic review, in order to verify which facilitators and barriers related to the home environment are capable of impacting motor resources and the participation of biological risk infants in the first year of life (Study I). This review analyzed that household environmental factors impacted motor resources in the first year of life, however, many factors were inconclusive or contradictory, and no studies were found that assessed their effects on participation at home. After completion of the review, gaps regarding the topic and the current pandemic scenario follow. Thus, Study II was designed with the objective of determining the impact of environmental factors during the COVID-19 pandemic, in the domains of motor resources and in the participation of biological risk infants in the home in the first year of life. Motor resources were assessed through the Alberta Infant Motor Scale (AIMS) and Infant Motor Profile (IMP) instruments, participation through the Participation and Environment Measure - Young Children (YC-PEM), and environmental factors through the instruments " Affordances in the Home Environment for Motor Development - Baby Scale" (AHEMD-IS), YC-PEM (general home environment), average monthly income assessed (ABEP) and by a questionnaire designed to verify the aspects of DS (COVID questionnaire) -19). The results showed that the home environment was a facilitator of motor skills, referring to greater maternal age, greater opportunity offered by the environment, associated with maternal education, higher family income, emotional and financial factors of SD and less need for physiotherapy interventions/guidance . However, for the outcome of involvement in participation, only maternal education and less need for physical therapy intervention/guidance were performance predictors. Thus, it is emphasized that environmental factors can have a peculiar impact on the functionality components, illustrating the need for a biopsychosocial assessment. Furthermore, this dissertation brings extremely relevant scientific, clinical and social contributions, since it will favor the optimization of evidence-based practice, in directing appropriate guidelines to families. This can help health professionals to implement strategies, through remote assessments and guidance that favor motor skills and the infant's participation in the home environment. In addition, early identification of the impact of environmental factors on the functionality of infants at biological risk will provide adequate and brief referral to biopsychosocial intervention.